Change in estrogenic activity in stored human urine before reuse as fertilizer - Maria Alejandra Arias; Ute Arnold; Heiner Goldbach (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Recycling of nutrients from human excreta may offer an opportunity for smallholder farms to improve crop nutrition and soil fertility. However, when applying human urine as fertilizer, it may load natural and synthetic estrogens into the environment. To avoid pollution by endocrine disruptors, treatment methods before field application must be implemented. The present study thus aims to evaluate the reduction in estrogenic activity in human urine during the storage period before urine is applied to the field. Method This study evaluated the estrogenic activity in diluted urine (DU) exposed to simulated sunlight (280â700 nm) and under dark conditions for 75 days. Estrogenic activity was analyzed using the recombinant yeast estrogen screen assay. Concentrations of total nitrogen (Ntot), ammoniumâN (NH4âN) and dissolved organic carbon were measured, as well as electrical conductivity and pH. Correlation of factors to the reduction of the estrogenic activity was also evaluated. Results Decay of estrogenicity occurred in both treatments, though it was faster in DU exposed to light (k=0.07 dayâ1) as compared to DU under darkness (k=0.05 dayâ1). Exposure of DU to a direct light source enhances decay of estrogenicity, however, losses of available N can be significant. Conclusion While reduction of estrogenic activity in DU stored under dark conditions takes longer, it is easy and does not require expensive equipment, energy sources or profound chemical expertise. Therefore, we suggest storage of DU under dark conditions as the best option for small-scale farmers and households in rural areas of developing countries.